Sosialisasi Pemanfaatan Fasilitas Perpajakan Pada UMKM di Kota Lamongan - Mesra Berlyn Hakim; Tri Winarsih; Nur Aini Maulidhia; Yahya Shidiq (Pusat Riset dan Inovasi Nasional, 2021)
The expected goal of this community service is that UMKM are able to understand the basics and regulations of taxation on UMKM so that UMKM business actors are able to fulfill their tax obligations. On the basis of the problems that occur with partners, this PKM program needs to be carried out by providing socialization regarding the existence of PP No. 23 of 2018 for MSMEs that have a turnover of below Rp. 4.8 billion in a year with a 0.5% tariff and only valid for 7 (seven) years. for private person and 3 years for UMKM entities. The method used is discussion and lecture. The service activities carried out by the PKM Team with the lecture and discussion methods have been able to add insight, motivation and understanding about the UMKM Final PPh in the future. UMKM actors are also expected to be disciplined and timely in reporting and paying and in accordance with applicable standards. And also with the UMKM tax incentives during the Covid 19 Pandemic, UMKM actors are expected to be able to use these incentives.